PESONA MORAL SASTRA POPULER PASCA TAHUN 2000-AN - Satriani, Irma; Ramadhani, Andi Reski; Salam, Aprinus; Dewi, Anita Candra (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
Personal morality is one of the important things in the existence of literature, not least in popular literature. Popular literature in Indonesia displays different moral faces from time to time. One of the dilemmas of moral issues is in presenting issues of ethnicity, religion, race, inter-group (SARA), and sex. This study questions how popular literature after the 2000s presents the morality of ethnicity, religion, violence, inter-group, and sex. These differences are possible because Indonesian society is increasingly educated and literate on the one hand, and when social media technology takes over "immoral things". This causes popular literature to manage the remaining morals that have been taken by social media more exclusively. This study will present several popular literature (novels) after the 2000s purposively. This study uses the theory of the concept of popular literature with a qualitative method of descriptive-analytical approach. The results of this study show that with the strengthening of the middle class in Indonesia which is increasingly educated and literate, its popular literature displays a more elegant “middle-class moral charm” in dealing with issues of ethnicity, religion, race, inter-group (SARA), and sex.